WHAT IS AN ADJECTIVE? - Sultonova Nozimaxon (Journal of new century innovations, 2023)
An adjective modifies a noun or a pronoun by describing, identifying, or quantifying words. An adjective usually precedes the noun or the pronoun which it modifies. In the following examples, the highlighted words are adjectives: The truck-shaped balloon floated over the treetops. Mrs. Morrison papered her kitchen walls with hideous wall paper. The small boat foundered on the wine dark sea. The coal mines are dark and dank. Many stores have already begun to play irritating Christmas music. A battered music box sat on the mahogany sideboard. The back room was filled with large, yellow rain boots.